Visible-Light-Mediated ipso-Carbosulfonylation of Alkynes: Synthesis of 3-Sulfonylspiro[4,5]trienones from Propiolamides and Sulfonyl Chlorides under Transition-Metal-Free Conditions - Liu, Yu; Wang, Qiao-Lin; Xiong, Bi-Quan; Zhang, Pan-Liang; Yang, Chang-An; Gong, Yan-Xia; Liao, Jing; Zhou, Quan (Synlett, 2018)
An efficient and convenient strategy to synthesize diverse 3-sulfonylspiro[4,5]trienones has been developed. This ipso-carbosulfonylation of alkynes proceeds by visible-light catalysis under transition-metal-free conditions and represents a new sulfonylation and ipso-cyclization of alkynes. In this transformation, the O atom in the newly generated carbonyl is derived from H2O and it features a broad substrates scope, especially for alkyl propiolamides and aliphatic sulfonyl chlorides.
Keywords: spiro compounds; difunctionalization; visible-light photoredox catalysis; propiolamides; sulfonyl chlorides